Your Heritage Will Still Remain : Racial Identity and Mississippi's Lost Cause - Goleman, Michael Jory (Book collections on Project MUSE., 2017)
"Your Heritage Will Still Remain details how Mississippians constructed their social identity in the aftermath of the crises that transformed the state beginning with the sectional conflict and ending in the late nineteenth century. The social identity studied in this book focuses primarily on how Mississippians thought of their place within a national context, whether as Americans, Confederates, or both. Even in the midst of secession, white Mississippians held firm to their American identity and easily transformed it into a Confederate identity that still venerated their American heritage. After the war, black Mississippians tried to etch their place within the Union and as part of American society, yet continually faced white supremacist backlash. During the period in question, radical transformations within the state forced all Mississippians to embrace, deny, or rethink their standing within the Union. Tracing the evolution of Mississippians' social identity from 1850 through the end of the decade uncovers why white Mississippians felt the need to create the Lost Cause legend and shaped the way they constructed it. With personal letters, diaries and journals, newspaper editorials, traveler's accounts, memoirs, reminiscences, and personal histories as its sources, Your Heritage Will Still Remain offers insights into the creation of Mississippi's Lost Cause and black social identity and how those cultural hallmarks continue to impact the state into the twenty-first century"--